Inklusi Keuangan, P2P Lending dan Kinerja UMKM: Peran Moderasi Literasi Keuangan - Aditya, Nathaniel Bima; Rita, Maria Rio (Ekonomis: Journal of Economics and Business, 2024)
This research aims to examine the influence of financial inclusion and peer to peer lending (P2P lending) on the performance of SMEs in the city of Salatiga, as well as testing the moderating effect of financial literacy. This research used 92 MSMEs in the city of Salatiga as the sample. Primary data were processed by using the Moderated Regression Analysis (MRA) technique. The study findings prove that: financial inclusion and P2P lending have a positive effect on MSME performance, then financial literacy strengthens the positive influence of financial inclusion and P2P lending on MSME performance. This study contributes to enriching literature in the field of financial management for MSMEs and can be a consideration for stakeholders and MSME players to improve business performance.